Use of alternative and complementary medicine in patients with malignant diseases in high-volume cancer center and future aspects - Davor Kust; Ivan Šamija; Jasmina Marić-Brozić; Branka Svetec; Marija Miletić; Gordana Mamić; Ante Bolanča; Zvonko Kusić; Ana Fröbe (Acta Clinica Croatica, 2016)
Usage of complementary and alternative medicine (CAM) is steadily increasing over the last decades, gaining medical, economic and sociological importance. The aim of the present study was to assess the use of complementary and alternative therapies in cancer patients. A crosssectional, descriptive survey design was used to collect data through an anonymous questionnaire. A total of 267 patients were included in the study. The prevalence of CAM use among cancer patients in this study was 60.3%. It was found that 61 heterogeneous CAM therapies were used, the most popular among patients being naturopathy/folk medicine. In multivariate logistic regression analysis, independent predictors of CAM use were high income, divorced status, female sex and younger age. In conclusion, considering the fact that a large proportion of patients used at least one CAM approach, we need to continue our efforts to improve the patient-oncologist communication in order to deliver most reliable information to patients and to better understand the possible standard medicine-CAM interactions. According to results of the latest studies, CAM therapies that help manage pain, nausea, fatigue, anxiety, and other symptoms should be integrated into the patient overall care.